2009
DOI: 10.1002/mus.21430
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine preserves skeletal muscle force during an inflammatory insult

Abstract: The purpose of this study was to test the hypothesis that acute glutamine (GLN) supplementation can counteract skeletal muscle contractile dysfunction occurring in response to inflammation by elevating muscle heat shock protein (Hsp) expression and reducing inflammatory cytokines. Mice received 5 mg/kg lipopolysaccharide (LPS) concurrently with 1 g/kg GLN or vehicle treatments. Plantarflexor isometric force production was measured at 2 hours post-injection. Blood and gastrocnemius muscles were collected, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
15
0
2
Order By: Relevance
“…Additional studies have shown that macrophages require high levels of Gln to successfully produce inflammatory mediators as part of the innate immune response for protection against intracellular pathogens (86). Consistent with this notion, results here show that there is a significant positive association between plasma Gln concentrations and HSP70 transcript levels measured in circulating white blood cells from children with malaria.…”
Section: Disclosuresupporting
confidence: 86%
“…Additional studies have shown that macrophages require high levels of Gln to successfully produce inflammatory mediators as part of the innate immune response for protection against intracellular pathogens (86). Consistent with this notion, results here show that there is a significant positive association between plasma Gln concentrations and HSP70 transcript levels measured in circulating white blood cells from children with malaria.…”
Section: Disclosuresupporting
confidence: 86%
“…Hind-limb plantarflexor isometric force-production was measured as previously described by our laboratory (Meador and Huey, 2009). Briefly, mice were anesthetized with a ketamine/xylazine (40/3 mg/ml) cocktail which was administered 0.1 ml per 25 g body weight i.p., and the sciatic nerve was exposed through the popliteal fossa in order to electrically stimulate the nerve and elict contraction of the plantarflexors.…”
Section: Methodsmentioning
confidence: 99%
“…Functional testing was completed to detect post-eccentric exercise injury in WT and ␣ 7Tg mice. Maximal isometric force of the plantarflexors was measured in situ as previously described (21) for each of the following groups: WT basal, ␣7Tg basal, WT 7D PE, and ␣7Tg 7D PE (n ϭ 5/grp). The forcemeasurement apparatus consisted of a servomotor and analog control unit (model 305C-LR, Aurora Scientific, Aurora, ON, Canada), a square-wave stimulator (model 2100, A-M Systems, Carlsborg, WA), and a PC running a customized LabView 8.2 program controlling the servomotor and stimulator.…”
Section: Animalsmentioning
confidence: 99%